Uslūb iltifāt dalam al-Qur’an Perspektif Afifuddin Dimyathi dalam Al-Syāmil fī Balāghah Al-Qur'ān - Ahmad Fathin Ghoyyatsusy Syafa'at Aly 'asyiqin (Jurnal Moderasi, 2026)
Uslūb iltifāt is one of the Qur’anic linguistic styles that receives particular attention in Balāghah studies due to its shifts in grammatical structure or pronouns, which enhance rhetorical effect and deepen meaning. Through his work Al-Syāmil fī Balāghah al-Qur’ān, Afifuddin Dimyathi presents an in-depth analysis of the function of iltifāt in enriching and reinforcing the messages of the Qur’an. This study aims to examine the interpretive methodology employed by Afifuddin Dimyathi and his analysis of uslūb iltifāt. Employing a qualitative-descriptive approach within a stylistic theoretical framework, the research reveals that Afifuddin utilizes a contextual analytical method grounded in authoritative classical sources, presented in a systematic and accessible manner. The findings indicate that Al-Syāmil fī Balāghah al-Qur’ān identifies three forms of iltifāt: iltifāt fī al-shiyāgh (shifts in sentence form), iltifāt fī al-dhamā’ir (shifts in pronouns), and iltifāt fī al-‘adad (shifts in number), while other types are not explicitly discussed.